The Implementation of Participation Principles in Good Governance - Mindarti, Lely Indah (Jurnal Ilmiah Administrasi Publik, 2016)
A Shift occurs on the development paradigm from the political development orientation, citizensâ€™ economy development paradigm up to local independence paradigm. With the participation, subsequently the development activities should be surely understood, not only considered as a responsibility but also require the citizensâ€™ participation in order to improve their life quality. Merjosari Village has the society participation channel in a form of a neighborhood group Savings and Loan named â€œSrikandiâ€ as an opportunity for the society to improve their local economy especially family economy. The result of the study showed that citizensâ€™ participation in neighborhood Group (RT) 06, Community Group (RW) 11, Merjosari Village, Lowokwaru District, Malang in increasing the family economy through Srikandi could be seen from a forum that accommodates society participation and capability to take a part so that it can continuously progress. The emphasis of Srikandi was on the economy development through informal sectors, such as on the small-scaled industries which can give multiplier effect in increasing family economy so that local independence can be reached.